Pelaksanaan Konseling Terhadap Ibu Hamil Perokok Pasif di Klinik Rika Hardi - Amrina Amran; Ika Putri Rahmadani (Jurnal Pengabdian Ilmu Kesehatan (JPIK), 2025)
Pregnant women who are exposed to cigarette smoke or become passive smokers have a high risk of experiencing pregnancy complications, such as premature birth and low birth weight (LBW). Many of them are unaware of these dangers, especially due to the lack of proper education. Counseling is necessary to help pregnant women understand the risks they face and to enable them to take preventive measures. This community service program was carried out at Clinic Rika Hardi, where it was found that several pregnant women were still exposed to cigarette smoke at home and had never received any related education. This condition became the main reason for conducting counseling to better safeguard the health of both mother and fetus. The risk factors for LBW are closely related to maternal health problems during pregnancy and childbirth, one of which is exposure to cigarette smoke during pregnancy. Cigarette smoke can affect fetal development because nicotine and carbon monoxide in cigarettes interfere with the transfer of nutrients from the mother to the fetus. This has a direct impact on fetal growth. Pregnant women who are exposed to cigarette smoke from family members at home are nine times more likely to give birth to a baby with low birth weight. Based on the results of the community service activity, 100% of participants were able to complete the evaluation questionnaire on the effectiveness of counseling activities using PowerPoint presentations and educational videos, and 100% participated in individual counseling sessions. It is expected that Rika Hardi clinic will be able to continue follow-up efforts for pregnant women who are passive smokers.